2020
DOI: 10.15414/jmbfs.2020.10.3.436-440
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antioxidant, Anti-Aging and Cytotoxicity Activity of the Essential Oils From Cinnamomum Zeylanicum

Abstract: Antioxidant activity, anti-aging effects and cytotoxicity activity of cinnamon essential oils from Cinnamomum zeylanicum were investigated in this study. The antioxidant activities of the cinnamon essential oil at the concentrations of 125, 250, 500, and 1000 µg/mL were determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2ʹ-azino-bis (3-ethylbenzo-thiazoline-6-sulfonic acid) diammonium salt (ABTS). The inhibitory activities against collagenase, elastase and tyrosinase were evaluated for anti-aging effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…EOCV at concentrations of 125, 250, 500 and 1000 µg/mL significantly increased the percentage inhibition of DPPH by 8.22 ± 0.70, 12.74 ± 2.48, 20.10 ± 1.71 and 28.74 ± 1.61%. At the same concentrations, the percentage inhibition of ABTS was 8.44 ± 1.19, 28.08 ± 2.19, 30.70 ± 1.33 and 50.17 ± 3.95%, respectively [50]. In addition, EOCVs showed inhibitory power against DPPH with a percentage inhibition of 94.42% at 8.0 µg/mL, and the IC50 was 0.245 µg/mL.…”
Section: Discussionmentioning
confidence: 82%
“…EOCV at concentrations of 125, 250, 500 and 1000 µg/mL significantly increased the percentage inhibition of DPPH by 8.22 ± 0.70, 12.74 ± 2.48, 20.10 ± 1.71 and 28.74 ± 1.61%. At the same concentrations, the percentage inhibition of ABTS was 8.44 ± 1.19, 28.08 ± 2.19, 30.70 ± 1.33 and 50.17 ± 3.95%, respectively [50]. In addition, EOCVs showed inhibitory power against DPPH with a percentage inhibition of 94.42% at 8.0 µg/mL, and the IC50 was 0.245 µg/mL.…”
Section: Discussionmentioning
confidence: 82%
“…Another study by Najar et al (2019) reported that C. zeylanicum EO was found to be effective against all the cell lines along IC 50 at 20 ppm, while it was more effective on K562with IC 50 value at 6 ppm and less effective on T47D (IC 50 at 56.1 ppm). While Wanakhachornkrai et al (2020) revealed that cinnamon nanosuspension had no cytotoxicity on human fibroblast cells at 100 g/mL concentrations, while 150 g/mL caused cytotoxicity. Khalisyaseen and Mohammed (2021) reported the HPLC analysis of ethanolic extract-based nanosuspensions of C. zeylanicum bark and revealed the cinnamaldehyde: 74.67 ppm, eugenol: 6.998 ppm quercetin: 42.687 ppm, lignin: 5.860 ppm) and some phenolic components concentration (kaempferol: 0.0122 ppm, gallic acid: 0.030ppm).…”
Section: Data Availability Statementmentioning
confidence: 97%
“…Collagenase and elastase are members of the MMPs family that degrade collagen network and breakdown elastin fibers, respectively. As a result, wrinkles appearance, loss of skin elasticity, and consequently skin aging occur [ 4 ]. Tyrosinase is the rate-limiting enzyme in melanin synthesis, and its overproduction results in melanin accumulation and various skin disorders, including hyperpigmentation, sagging, wrinkles, freckles, and age spots.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the breakdown of hyaluronic acid by hyaluronidase results in skin drying and sagging and loss of skin smoothness and plasticity [ 6 ]. Therefore, medical and cosmetic preparations used to protect skin against aging and hyperpigmentation are mainly composed of collagenase, tyrosinase, elastase, and hyaluronidase inhibitors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%